BECA : An Android Aplication to Increase Breast Self-Examination (BSE) Practice - Ratna Puspita Adiyasa; Resta Betaliani Wirata (International Journal of Nursing and Health Services (IJNHS), 2021)
Cancer is one of the chronic diseases that could decrease productivity dan quality of human sources due to its long term treatment, including breast cancer. Breast self-examination (BSE) should be done as early detection for breast cancer. The use of technology is needed to achieve this goal. The purpose of this study was to determine the effect of a BSE application android called BECA on BSE practice. This study utilized quantitative and quasi-experimental design without a control group. The study was conducted in a selected area in Yogyakarta. The respondents were selected via purposive sampling. The BSE practice was assessed used a BSE practice form and statistically tested with the Wilcoxon test. The total number of respondents of this study was 32 women childbearing aged. The characteristic of respondents were 20-30 years old (53.1%), married (68.8%), housewife (43.8%), and senior high school (56,3%). Wilcoxon test results showed a computed p-value of 0.000 so that the null hypothesis was rejected. In conclusion, BECA application android is effective to improve the BSE practice. The researchers recommend utilizing BECA Application android for daily use.